2018
DOI: 10.5664/jcsm.7116
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Single and Multiple Suicide Attempters: What Nightmares Can Tell Us That Other Predictors Cannot

Abstract: Inconsistent with past research, this study showed that nightmare frequency, and not nightmare chronicity or severity/distress, differentiated between single and multiple suicide attempters. This outcome suggests that the number of nightmares experienced may be more pertinent in predicting repeat suicide attempts than their duration or perceived severity. Study limitations include a cross-sectional design, a convenience sampling approach, a lack of control for previous treatment or length of time since last at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 34 publications
2
8
0
Order By: Relevance
“…We found an association between anxiety-induced sleep disturbance and MSA. Similarly, in a previous study 3 among adults, an association was found between the frequency of nightmares and MSA. Knowledge of the variables that are potentially associated with subsequent suicide attempts can be helpful to healthcare providers, who could detect anxiety-induced sleep disturbance, lack of close friends and loneliness to identify MSA risk.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…We found an association between anxiety-induced sleep disturbance and MSA. Similarly, in a previous study 3 among adults, an association was found between the frequency of nightmares and MSA. Knowledge of the variables that are potentially associated with subsequent suicide attempts can be helpful to healthcare providers, who could detect anxiety-induced sleep disturbance, lack of close friends and loneliness to identify MSA risk.…”
Section: Discussionsupporting
confidence: 72%
“…Asking about anxiety-induced sleep problems and loneliness may be less threatening than asking about suicidal ideation or intent. 3 Furthermore, low parental support was among girls associated with MSA in this study. In the 2012 GSHS in Argentina, parental support was found to be protective against suicide attempts.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…It is known that SB is a complex disorder, which involves many environmental, behavioral, neurobiological, and genetic factors (Gvion & Levi‐Belz, ; Speed, Drapeau, & Nadorff, ). Researchers of suicide behavior are looking for predisposing (distal) and precipitating (proximal) factors (Conejero, Olie, Courtet, & Calati, ; Gerada, ; Gvion & Levi‐Belz, ; Speed et al, ). Besides, there are several biological, genetic, and environmental abnormalities have been reported in SB, but it is not clear which ones are risk factors (Fiori et al, ; Schneider et al, ).…”
Section: Discussionmentioning
confidence: 99%